THE EFFECT OF WARM NECK COMPRESS APLICATION ON REDUCING HEADACHE INTENSITY IN ELDERLY PATIENTS WITH HYPERTENSION : PENGARUH PEMBERIAN KOMPRES HANGAT PADA LEHER TERHADAP PENURUNAN INTENSITAS NYERI KEPALA PADA LANSIA HIPERTENSI - Octavia, Lisa; Nur Kholifah, Siti; Miadi; Adinata, Ach. Arfan (Jurnal Keperawatan Terapan, 2025)
Degenerative diseases that remained a global issue included hypertension. One of the signs and symptoms of hypertension was headache caused by vascular damage throughout the peripheral blood vessels. Warm compresses were one method of pain management for increase muscle relaxation, thus enhancing circulation and boosting the supply of oxygen and nutrients to the tissues. This study aimed to determine the effect of warm neck compress aplication on reducing headache intensity in elderly patients with hypertension. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 elderly individuals with hypertension. The dependent variable was headache intensity and the independent variable was the application of warm compresses. The measuring instrument used was the pain intensity assessment instrument Wong-Baker FACES Foundation, 2016. Data analysis was conducted using the Wilcoxon signed-rank test. There was a significant the effect of warm neck compress aplication on reducing headache intensity in elderly patients with hypertension (p=0.000<0.05), as evidenced by the results showing that before the intervention, the majority of patients experienced severe pain (60%), and after the intervention the majority experienced mild pain (60%). Therefore, warm compresses could be recommended as supportive therapy in the management of hypertension in the elderly.